The handbook of communication and corporate social responsibility - Ihlen, $1#[Y(Bnd.s; Bartlett, Jennifer; May, Steve (Steve Kent), 1961- (Malden, MA : Wiley-Blackwell, 2011)
'This book represents the definitive research collection for corporate social responsibility communication, offering cross-disciplinary and international perspectives from the top scholars in the field. Addresses a gap in the existing CSR literature Demonstrates the relevance of effective CSR communication for the management of organizations The 28 contributions come from top scholars in public relations, organizational communication, reputation management, marketing and management'--
'While there is a huge amount of literature on corporate social responsibility (CSR), there is relatively little advice to be found regarding how CSR should be communicated. This book represents the definitive research collection for CSR communication, taking stock of the existing recommendations and demonstrating how the communication disciplines can make contributions to central research gaps in the CSR literature. Contributions from leading scholars in public relations, organizational communication, reputation management, marketing and management show how theories of discourse, internal communication, cognitive psychology, reputation and rhetoric enrich our understanding of CSR communication and how this influences the way organizations should be managed'--
Includes bibliographical references and index.
Keywords: Social responsibility of business; Mass media and business; Business communication